Optimizing Catalyst Loading for Improved Quality of SF-05 in Hydrocracker Reactor C-3-03B at HCU RU V Balikpapan - Adi Sampurno; Totok Eka Suharto; Zahrul Mufrodi (Universitas Ahmad Dahlan, 2025)
PT Kilang Pertamina Internasional RU V Balikpapan innovated the Unibon Hydrocracker unit to increase the production of Smooth Fluid (SF-05), a high-quality base oil for drilling mud. Because the catalyst was approaching the end of run and the product did not yet meet specifications, the catalyst (Change of Catalyst - COC) was replaced with a new configuration in Reactor I C-3-03B. This research aims to optimize the hydrocracking process by changing catalyst loading and operating settings for the C-3-16B fractionation column. It is hoped that this effort will produce high-quality SF-05, meet market demand, and increase efficiency and environmental friendliness. The research results show that the Smooth Fluid SF-05 product meets all specifications with an average hydrogen consumption of 231,649 Nm3/m3 (purity 94.83%) in the HCU Train B reactor. This condition helps improve the quality of products that are more competitive in the market, thus having a positive impact on increasing company profits. Hydrogen consumption is influenced by various process variables and increases with changes in hydrogen partial pressure, CFR, H2/HC ratio, conversion rate, WABT, and LHSV. All process variables are still within the specified operating design range.